Flexible fabric-based GaAs thin-film solar cell for wearable energy harvesting applications - Yun, Yeojun; Moon, Sunghyun; Kim, Sangin; Lee, Jaejin (Solar Energy Materials and Solar Cells, 2022)
GaAs photovoltaic (PV) cells have been extensively studied for flexible energy harvesting devices due to their merits such as thin-film feasibility, flexibility, and high-efficiency. However, GaAs-based thin-film PV cells have a limitation for the applications in wearable platform since they are not compatible with fabric carrier. To handle this problem, we report thin-film transfer technique that involves a sacrificial layer with a double-layer structure, an Au–Au bonding technique, a Cr/Au bilayer to induce metal stress, and an etchant for fast epitaxial lift-off (ELO). In addition, a polyimide layer attached underneath the fabric substrate not only protects the fragile epi layer but also accelerates the lateral etching via spontaneous bending. The application of these techniques enables the successful transfer of GaAs thin-film PV epi structures onto fabric platform without degrading crystal quality. Fabric-based GaAs PV cells are fabricated via the standard PV cell fabrication process. The platform expansion of GaAs thin-film techniques has great potential for large-scale commercialization.
Keywords: Energy harvesting device; Epi transfer; Flexible gaas solar cell; GaAs solar cells; GaAs thin films; Higher efficiency; Large air gaps; Thin-film photovoltaic cells; Thin-films; Wearable devices; Epi transfer; Fabric; Flexible GaAs solar cell; Large air gap; Wearable device